Influence of shame on young consumers’ purchase intentions: A social sustainability perspective - Frensel, Anna Maria; Landmann, Elisa; Schönitz, Marie‐Sophie; Siems, Florian U; Sharma, Piyush (Emerald, 2025)
Purpose This paper aims to explore the influence of social frame (worker vs animal rights), product category (hedonic vs utilitarian) and social presence (similar age, younger and older) on expected shame and purchase intentions for sustainable products.